Speed Estimation Using an Inertial Measurement Unit with Convolutional Neural Networks - Bachir, Zainab Raafat (2019)
A Master of Science thesis in Electrical Engineering by Zainab Raafat Bachir entitled, “Speed Estimation Using an Inertial Measurement Unit with Convolutional Neural Networks”, submitted in May 2019. Thesis advisor is Dr. Usman Tariq. Soft and hard copy available.